2008
DOI: 10.19030/jdm.v3i4.4998
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Practices In Universities Of Pakistan

Abstract: Decision making can be regarded as an outcome of mental processes (cognitive process)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…This is consistent with the results of Mazhar and Akhtar's (2016) study. The study found that private universities were more satisfactory regarding experienced managers availability, their managers were more proficient because most of the private universities hire the services of retired personnel who have greater managerial experiences as compared to public universities and there was a strong check and balance mechanism (Anwar, 2008;Naz, 2013). It is observed that political intervention was exercised in public sector universities.…”
Section: Discussionmentioning
confidence: 93%
“…This is consistent with the results of Mazhar and Akhtar's (2016) study. The study found that private universities were more satisfactory regarding experienced managers availability, their managers were more proficient because most of the private universities hire the services of retired personnel who have greater managerial experiences as compared to public universities and there was a strong check and balance mechanism (Anwar, 2008;Naz, 2013). It is observed that political intervention was exercised in public sector universities.…”
Section: Discussionmentioning
confidence: 93%
“…Decision making practice is found similar in both sectors public and private. (Anwar, 2008). Investigated unsatisfactory condition about decision making practice in universities of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Step 10: Job Offer (faculty recruitment and selection guide, www.google.com) "Decision making can be regarded as an outcome of mental processes (cognitive process) leading to the selection of a course of action among several alternatives." (Anwar, 2008) According to Matthai et al, (cited by (Anwar, 2008), the university has its apex levels bodies such as senate, syndicate, academic council, faculties and board of studies, planning committees to take decisions. It has the administrators like Vice Chancellor, registrar, provost, deans, Directors, and head of the departments.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidence showed that the quality of teachers cannot be orchestrated without a strong teacher education system (Anwar, Yousuf, & Sarwar, 2008). A teacher education system that produces professionally fit human capital is the output of quality teaching and learning; therefore to compete in the evolution of digital technology, the education sector should be in concordance with the 21st-century advancement (Dali, Burgess, & Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%